2016
DOI: 10.1177/1475090216642468
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds-averaged Navier–Stokes simulation of hydrofoil effects on hydrodynamic coefficients of a catamaran in forced oscillation

Abstract: Determination of high-speed crafts' hydrodynamic coefficients will help to analyze the dynamics of these kinds of vessels and the factors affecting their dynamic stabilities. Also, it can be useful and effective in controlling the vessel instabilities. The main purpose of this study is to determine the coefficients of longitudinal motions of a planing catamaran with and without a hydrofoil using Reynolds-averaged Navier-Stokes method to evaluate the foil effects on them. Determination of hydrodynamic coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The results showed that increasing the frequency caused to decrease this coefficient and tends to a constant value. 24 Reviewing published researches, one can see lack of using research outcomes in constructed vessels. In this research, the authors tried to implement the extracted results from laboratory in the main vessel and had been tried to extract the new results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that increasing the frequency caused to decrease this coefficient and tends to a constant value. 24 Reviewing published researches, one can see lack of using research outcomes in constructed vessels. In this research, the authors tried to implement the extracted results from laboratory in the main vessel and had been tried to extract the new results.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that increasing the frequency caused to decrease this coefficient and tends to a constant value. 24…”
Section: Introductionmentioning
confidence: 99%